Positive Deviance Behavior Towards Stunting Prevention in Gunung Maddah Sampang Village - Dewi, Septishiya Tri Charisma; Rachmayanti, Riris; Riswari, Aninditya Ardhana; Diana, Rian; Khomsan, Ali; Riyadi, Hadi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
The high prevalence of stunting is a major nutritional problem that must be resolved because it is a threat to the future of Indonesian children. One of the efforts to prevent stunting needs to be done by searching for solutions that can be practiced by the general public by applying positive deviance to improve behavior in fulfilling nutritional content in pregnant women and children. The purpose of this research is to identify and study positive deviance behavior to prevent stunting. The research method used is the qualitative method. The research was conducted for 28 months (February 2020-June 2022) in Gunung Maddah Village, Sampang Regency, Madura Island, East Java, Indonesia. Data collection techniques included the results of Focus Group Discussions (FGDs), in-depth interviews, and observations obtained from 55 informants including mothers of toddlers, parents/parents-in-law, community members, cadres, and health workers. Data analysis techniques included content analysis consisting of data preparation, data editing, and data cleaning. The results showed that positive deviance behavior to prevent stunting in Gunung Maddah Sampang Village included the consumption of milk by pregnant women, the provision of milk to children (breast milk and/or cow's milk), mothers' efforts to overcome eating difficulties, limiting and regulating children's snacking habits, and the consumption of rice with vegetables and side dishes.